LONG-COURSE ORAL CORTICOSTEROID TOXICITY IN CHILDREN. Issue 9 (17th August 2016) - Aljebab, Fahad; Choonara, Imti; Conroy, Sharon
Abstract : Background: Long courses of oral corticosteroids are commonly used in children in the management of conditions such as nephrotic syndrome, leukaemia, asthma and others. Various adverse drug reactions (ADRs) are known to occur with their use. This systematic review aimed to identify the most common and serious ADRs and to determine their relative risk levels. Methods: A literature search of several databases; Embase, Medline, International Pharmaceutical Abstracts, CINAHL, the Cochrane Library and PubMed was performed to identify all studies where corticosteroids had been administered to paediatric patients ranging from 28 days to 18 years of age for at least 15 days of treatment. Each database was searched from their earliest dates to March 2014. All types of studies that provided clear information on ADRs were included. Results: 91 relevant studies were found from 27 countries. These studies represented a total of 6653 children and contained reports of 4124 ADRs, the majority in patients with leukaemia, haemangioma and asthma. Oral prednisolone was the most commonly prescribed corticosteroid (74% of patients). The three most frequent ADRs were weight gain, Cushingoid features and growth retardation. The incidence rates of patients with these three ADRs were 22.4%, 20.6% and 18.9%, respectively. Increased susceptibility to infection was the most serious ADR. 24 children died from infections, ten from varicella zoster and the others from different microorganisms. Conclusions: Weight gain, Cushingoid features and growth retardation were the most frequent ADRs seen when long-course oral corticosteroids were given to children. In addition, increased susceptibility to infection was the most common cause of mortality.